2019
DOI: 10.1101/648865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Salmonella LysR family regulator, RipR, activates the SPI-13 encoded itaconate degradation cluster

Abstract: 8Itaconate is a dicarboxylic acid that is able to inhibit the isocitrate lyase enzyme of the 9 bacterial glyoxylate shunt. Activated macrophage have been shown to produce itaconate, 10 suggesting that these immune cells may employ this metabolite as a weapon against invading 11 bacteria. Here we demonstrate that itaconate can exhibit bactericidal effects under acidic 12 conditions resembling the pH of a macrophage phagosome. In parallel, successful pathogens 13 including Salmonella have acquired a geneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Bacterial growth is well known to be affected by pH [29][30][31], and failure to ensure a constant pH may considerably skew MIC measurements. Recent reports have also suggested that there may be synergy between pH and itaconate activity [32,33], although a systematic exploration of the phenomenon has yet to be reported. We elected to perform studies with Escherichia coli (a species that does not encode itaconate-degrading enzymes) and Salmonella enterica ser.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial growth is well known to be affected by pH [29][30][31], and failure to ensure a constant pH may considerably skew MIC measurements. Recent reports have also suggested that there may be synergy between pH and itaconate activity [32,33], although a systematic exploration of the phenomenon has yet to be reported. We elected to perform studies with Escherichia coli (a species that does not encode itaconate-degrading enzymes) and Salmonella enterica ser.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that small organic acids are capable of inhibiting bacterial growth at low pH values, potentially via a "proton shuttle" effect. [69][70][71] With addition of an organic acid to growth medium, the pH decreases, favoring the protonated (uncharged) form of the acid, which may cross bacterial membranes more easily (Figure 3). Once inside the (less acidic) bacterial cytosol, the organic acid releases a proton, thereby reducing the cytosolic pH and causing toxicity.…”
Section: Antimicrobial Activity Of Itaconatementioning
confidence: 99%
“…However, organic acids have different toxicities that do not always correlate well with their respective pKa values, [72][73][74][75] implying that the exact molecular structure of the organic acid may lead to specific toxicity effects. Itaconate is known to have more potent antimicrobial activity at lower pH values, 60,71,76 and this has recently been investigated in more detail. 60 By comparing the MIC of itaconic acid with that of its sodium salt, Duncan et al demonstrated that the decrease in pH caused by itaconic acid addition to the growth medium increases the antimicrobial activity of itaconate against numerous bacterial species.…”
Section: Antimicrobial Activity Of Itaconatementioning
confidence: 99%
See 2 more Smart Citations